2012
DOI: 10.1192/apt.bp.110.008714
|View full text |Cite
|
Sign up to set email alerts
|

Supported accommodation for people with severe mental illness: an update

Abstract: SummaryAppropriate housing and support are essential elements in the care of many people with mental health problems, and housing has a major impact on the quality of their lives. In the post-deinstitutionalised services of most high-income countries, a complex range of supported accommodation is available, mostly in the private (for-profit and not-for-profit) sector. We describe the different forms of accommodation and consider recent trends in policy and practice and the evidence base in this area. We also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Finally, housing satisfaction acts as a variable in determining the relationship between the resident's background and his attitude towards mobility. In another clime, Research has shown that living in socially undesirable housing has adverse social and psychological effects [31,33,81,89,107]. Also, [81] revealed poor housing to be held responsible for some social problems, including identifiable physical and mental diseases of occupants' maladjustments of different kinds, intra-family and inter-family crowding, low self-esteem of slum dwellers, barriers to economic improvement, the problem of adequately educating the children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, housing satisfaction acts as a variable in determining the relationship between the resident's background and his attitude towards mobility. In another clime, Research has shown that living in socially undesirable housing has adverse social and psychological effects [31,33,81,89,107]. Also, [81] revealed poor housing to be held responsible for some social problems, including identifiable physical and mental diseases of occupants' maladjustments of different kinds, intra-family and inter-family crowding, low self-esteem of slum dwellers, barriers to economic improvement, the problem of adequately educating the children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, almost half the users of both the English and Verona services moved on to more independent accommodation successfully over the 30 months. This suggests that, in both settings, a 'care pathway' was in operation where individuals graduate to more independent accommodation over time, as they gain skills and confidence [21].…”
Section: Service User Characteristics Confirmed That Supported Accommmentioning
confidence: 99%
“…Whilst the specification of the three main models of service in the two countries are not exactly the same, in both they tend to operate as a 'care pathway', providing an appropriate level of support to individuals according to their specific needs, and, where possible, enabling them to move on to less supported or fully independent accommodation over time. This has the advantage of providing tailored support and clear goals for staff and service users to work towards, but the drawback is that individuals have to keep moving home as they progress in their recovery [21]. In 2016, in England, it is estimated that around 60,000 working-age adults with severe mental health problems are living in supported accommodation (roughly 100/100,000 inhabitants), costing around £150 per week for the lowest supported accommodation services (FO) to around £500 per week for the highest (RC) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Studying mental health-supported accommodations is hampered around the world by a confusion of terms 2 and characteristics, such as models, physical structures, and recovery focus (33, 34). A recent effort to create a taxonomy identified at least five different international types varying along dimensions of staffing location, level of support, permanence, physical setting (35).…”
Section: Introductionmentioning
confidence: 99%